STUDIES ON BOVINE CONGENITAL INTERNAL HYDROCEPHALUS IN A NEW BORN COW CALF - JANA, DEBASIS; GHOSH, MOUSUMI (The Indian Journal of Animal Reproduction, 2023)
A case of congenital internal hydrocephalus in a new born indigenous calf and its successfulm therapeutic management has been reported.
Keywords: Hydrocephalus; Congenital; Calf